(untitled) (International Current Pharmaceutical Journal, 2013)
The purpose of the present study was to prepare, characterize and evaluate the colon-targeted microspheres of mesalamine for the treatment and management of ulcerative colitis (UC). Microspheres were prepared by the ionic-gelation emulsification method using tripolyphosphate (TPP) as cross linking agent. The microspheres were coated with Eudragit S-100 by the solvent evaporation technique to prevent drug release in the stomach. The prepared microspheres were evaluated for surface morphology, entrapment efficiency, drug loading, micromeritic properties and in-vitro drug release. The microspheres formed had rough surface as observed in scanning electron microscopy. The entrapment efficiency of microspheres ranged from 43.72%-82.27%, drug loading from 20.28%-33.26%. The size of the prepared microspheres ranged between 61.22-90.41µm which was found to increase with increase in polymer concentration. All values are statistically significant as p<0.05. Micromeritic properties showed good flow properties and packability of prepared microspheres. The drug release of mesalamine from microspheres was found to decrease as the polymer concentration increases. The release profile of mesalamine from eudragit-coated chitosan microspheres was found to be pH dependent. It was observed that Eudragit S100 coated chitosan microspheres gave no release in the simulated gastric fluid, negligible release in the simulated intestinal fluid and maximum release in the colonic environment. It was concluded from the study that Eudragit-coated chitosan microspheres were promising carriers for colon-targeted delivery of Mesalamine. DOI: http://dx.doi.org/10.3329/icpj.v2i3.13577 International Current Pharmaceutical Journal, February 2013, 2(3): 42-48